Clinical Validity of Detecting Circulating Tumor Cells by AdnaTest Assay Compared With Direct Detection of Tumor mRNA in Stabilized Whole Blood, as a Biomarker Predicting Overall Survival for Metastatic Castration-Resistant Prostate Cancer Patients. Issue 5 (September 2016) - Danila, Daniel C.; Samoila, Aliaksandra; Patel, Chintan; Schreiber, Nicole; Herkal, Amrita; Anand, Aseem; Bastos, Diogo; Heller, Glenn; Fleisher, Martin; Scher, Howard I.
Abstract : Abstract: Circulating tumor cell (CTC) number measured with the CellSearch assay is prognostic for survival in metastatic castration-resistant prostate cancer before and after therapy. Using a standard operating protocol for sample collection, processing, and analysis, we compared detection rates of CellSearch performed using US Food and Drug Administration–cleared methodology with a second positive selection assay, AdnaTest, and a nonselection polymerase chain reaction (PCR)–based (direct detection PCR [DDPCR]) assay in 55 blood samples from 47 men with progressive metastatic castration-resistant prostate cancer. AdnaTest requires processing within 4 hours of the draw and detects KLK3, PSMA, and EGFR transcripts in cells captured on magnetic beads. The DDPCR assay can be processed up to 7 days after a draw and detects KLK2, KLK3, HOXB13, GRHL2, and FOXA1 genes. AdnaTest and DDPCR were considered positive if at least 1 transcript was detected. AdnaTest detected CTCs in 34 samples (62%; 95% confidence interval [CI], 48%–75%), of which 23 (68%) had unfavorable CTC counts by CellSearch. A positive DDPCR result was seen in 38 cases (69%; 95% CI, 55%–81%), including 24 (63%) with unfavorable CellSearch CTC counts. CellSearch found unfavorable CTC counts in 25 samples (45%; 95% CI, 33%–58%). Sensitivities were similar between the AdnaTest and DDPCR assays, and both were more sensitive than CellSearch. Concordance probability estimates (possible values, 0.5–1.0) associating the biomarker result with survival were similar: 0.77 (SE, 0.07) for AdnaTest, 0.72 (SE, 0.08) for DDPCR, and 0.76 (SE, 0.06) for CellSearch. Overall detection rates between the AdnaTest and DDPCR assays were similar, and both were superior to CellSearch. The DDPCR assay required the lowest blood volume, least on-site processing, and longest stability for batch processing. Abstract : Supplemental digital content is available in the text.